The dialogue between the courts revisited - Mulder, Jule (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2025)
This article explores the dialogue between the CJEU and national courts on the scope and meaning of religious discrimination under Framework Directive 2000/78/EC. Focusing on two main emerging strands of case law concerned with (1) neutrality policies banning religious symbols at work and (2) the internal autonomy of religious organisations, and drawing together insights from integration studies and critical comparative law; the analysis explores how national courts framed, explained and presented their preliminary references and how this potentially impacted CJEU judgments. Using the preliminary reference procedure, national courts from three jurisdictions repeatedly asked the CJEU very similar questions, to clarify, challenge or confirm the Court’s approach with various degrees of success. Three common strategies emerge. National courts ask questions via the preliminary reference procedure to shelter national law from EU influences; they rely on EU law to empower themselves domestically; and, occasionally, they reach out to influence the development of EU law. In the latter case, the dialogue seems to be most challenging in the context of religious discrimination, as self-referential national courts often struggle to fully engage with the EU legal framework and to provide a convincing argument to the CJEU. While not conclusive in isolation, the findings provide another piece of knowledge in our quest to understand the apparent stagnation of EU non-discrimination law and the CJEU case law on religious discrimination, which has attracted significant criticism from academia and practice.
Keywords: delovna mesta; dialog sodišč; nacionalna sodišča; pravo EU; predhodno odločanje; Sodišče EU; verska diskriminacija; verska svoboda